Repeated sprint and change-of-direction abilities in soccer players: effects of age group - Dellal, A.; Wong, Del P. (The Journal of Strength and Conditioning Research, 2013)
The purpose of the present study was to compare the performance in repeated sprint ability (RSA) and repeated changes-of-direction (RCOD) among elite soccer players with different age categories. Forty-nine elite soccer players from the same club and from different age categories (Pro2: n = 8, U19: n = 18, U17: n = 13, and U15: n = 10) participated in this study. Each player was tested in both a RSA straight-line sprints (10 × 20 m with active recovery) and a RCOD test including four 100° COD at every 4 m (10 × 20 m with active recovery). The average time (AT), fastest time (FT), total time (TT), percentage of decrement score (%Dec), and RSA/RCOD index were recorded and calculated during all the RSA and RCOD tests. Results showed significant age group effects on RSA and RCOD parameters (p < 0.01) and RSA/RCOD index parameters (p < 0.01). Compared with other groups, U15 has significant (p < 0.05) higher values in RSA-AT, RSA-FT, RSA-TT, RCOD-AT, RCOD-FT, RCOD-TT, index-AT, index-FT, and index-TT. However, the trend of performance time and RSA/RCOD index was always similar (i.e., U15 > U17 > U19 > Pro2; Pro2 > U19 > U17 > U15) showing an age dependant for RSA and RCOD performance. The %Dec in RSA of U15 and U17 was significantly (p < 0.05) higher than U19 and Pro2, whereas the %Dec in RCOD of U15 was significantly (p < 0.05) higher than U19. In conclusion, the present study showed that the RSA and RCOD are age dependent, and therefore, coaches should plan a specific program differentiating the RSA and RCOD, while the individualized training could begin in U17.